Grid-Map-Based Self-Recovery (GSR) Method with Minimized Redundant Area in WSN - Kim, Doyoon; Lee, Minwoo; Lim, Jaesung (Journal of Korean Institute of Communications and Information Sciences, 2021)
With the recent development of IoT technology, the utilization of WSN has been diversified. The use of WSN is increasing in emergent situations such as disaster environments and the search for missing persons. So WSN's research is also actively underway. Among them, many studies have been conducted on the economical node deployment of WSNs. However, the loss of a node can occur at any time, resulting in a hole. This hole causes a number of problems in operating WSN. In this paper, we propose an algorithm to recover big holes and have minimal overlap area. This technique has the effect of leveraging a grid-based hole detection method to relocate the entire node and minimizes the overlapping area. When applied to big holes in simulations using MATLAB simulators, that shows great effectiveness in terms of overlapping area and overall coverage ratio. The proposed technique is a big hole recovery technique that can economically recover the big hole.
Keywords: Big Hole; Grid-Map; Node Deployment; Self-Recovery; Wireless Sensor Network